Use of Ion-Association Reactions for the Spectrophotometric Determination of Quetiapine - Sudha Lakshmi, P.B.; Rambabu, C. (Asian Journal of Chemistry, 2012)
Two simple and sensitive spectrophotometric methods (A and B) for the assay of quetiapine as fumarate in pure and dosage forms based on the formation of chloroform soluble ion-associates under specified experimental conditions are described. Two acidic dyes namely tropaeoline ooo (method A) and naphthol blue black (method B) are utilized. The formed complexes showed absorbance maxima at 480 nm and 590 nm for method A and method B respectively. Beer,s law is obeyed in the concentration range 4.0-20 and 2.2-10 μg/mL with molar absorptivity of 1.24 × 104 and 3.13 × 104 L mol-1 cm-1 respectively. These methods are found to be suitable for the assay of quetiapine in pharmaceutical formulations. The results of analysis have been validated statistically and by recovery studies.